2021
DOI: 10.3390/microorganisms9081727
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Study of Gut Microbiota in Infected and Colonized Subjects by Clostridiodes difficile

Abstract: Clostridiodes difficile can lead to a range of situations from the absence of symptoms (colonization) to severe diarrhea (infection). Disruption of gut microbiota provides an ideal environment for infection to occur. Comparison of gut microbiota of infected and colonized subjects could provide relevant information on susceptible groups or protectors to the development of infection, since the presence of certain genera could be related to the inhibition of transition from a state of colonization to infection. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 44 publications
3
3
1
Order By: Relevance
“…These contradictions in the literature may be due to the different methodologies used for sample extraction, amplification, and analysis, together with the limited number of samples processed. Consistent with other observations in the literature, we also found a decrease in Actinobacteria and an increase in Proteobacteria in patients with CDI compared to healthy individuals ( Amrane et al., 2019 ; Han et al., 2019 ; Han et al., 2020 ; Sánchez-Pellicer et al., 2021 ). When we assessed the genera by groups, we found that Ruminococcus , Clostridium _IV, Streptococcus , Acinetobacter , and Megamonas decreased in the CDI group compared to CDI.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…These contradictions in the literature may be due to the different methodologies used for sample extraction, amplification, and analysis, together with the limited number of samples processed. Consistent with other observations in the literature, we also found a decrease in Actinobacteria and an increase in Proteobacteria in patients with CDI compared to healthy individuals ( Amrane et al., 2019 ; Han et al., 2019 ; Han et al., 2020 ; Sánchez-Pellicer et al., 2021 ). When we assessed the genera by groups, we found that Ruminococcus , Clostridium _IV, Streptococcus , Acinetobacter , and Megamonas decreased in the CDI group compared to CDI.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with the literature, the lowest diversity and richness values were recorded for patients with R-CDI (Chang et al, 2008;Allegretti et al, 2016;Gazzola et al, 2020). Both our data and that of other authors show the existing damage to the microbiota or dysbiosis in patients with diarrhea due to C. difficile or other causes and that of patients colonized by C. difficile (Sangster et al, Sokol et al, 2018;Crobach et al, 2020;Sańchez-Pellicer et al, 2021;Wan et al, 2022). In addition, the greater damage to the microbiota in patients with repeated episodes of CDI is highlighted.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations